Beyond the canonical strategies of horizontal gene transfer in prokaryotes. (August 2017) - García-Aljaro, Cristina; Ballesté, Elisenda; Muniesa, Maite
Highlights: The reported diversity of HGT strategies in prokaryotes has recently increased. HGT could require MGE or be MGE-independent. Some MGE only mobilize their own DNA while others mobilize host DNA. Non-canonical strategies must be considered to evaluate the real extent of HGT in prokaryotes. Abstract : Efforts to identify and characterize strategies for horizontal gene transfer (HGT) in prokaryotes could have overlooked some mechanisms that do not entirely fit in with the canonical ones most often described (conjugation of plasmids, phage transduction and transformation). The difficulty in distinguishing the different HGT strategies could have contributed to underestimate their real extent. Here we review non classical HGT strategies: some that require mobile genetic elements (MGEs) and others independent of MGE. Among those strategies that require MGEs, there is a range of newly reported, hybrid and intermediate MGEs mobilizing only their own DNA, others that mobilize preferentially bacterial DNA, or both. Considering HGT strategies independent of MGE, a few are even not restricted to DNA transfer, but can also mobilize other molecules. This review considers those HGT strategies that are less commonly dealt with in the literature. The real impact of these elements could, in some conditions, be more relevant than previously thought.